Revolutionizing accounting with Artificial Intelligence / Musliha Musman, Salwa Muda and Raziah Bi Mohamed Sadique - Musman, Musliha; Muda, Salwa; Mohamed Sadique, Raziah Bi (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Artificial intelligence (AI) is an evolving technology with the potential to transform numerous industries and professions, including accounting. AI is a discipline of computer science that focuses on creating systems capable of executing activities that would normally need human intelligence (Boden, 2016). These tasks include learning, thinking, problem solving, language comprehension, and pattern recognition (Goertzel, 2021). AI systems change and grow over time, becoming more efficient at handling complicated tasks. This advanced technology is expected to compel accountants and other stakeholders in the accounting profession to realize AI's disruptive impact, resulting in a variety of diverse and complex implications for the future of the accounting profession (Anomah et al., 2024).